Evaluación técnico-financiera para la implementación de un sistema de neutralización para el tratamiento del lixiviado de carbón en la central Termozipa (2018)
In the present project, a proposal was made for the implementation of a neutralization system in the treatment of coal leachate; This leachate is generated continuously by the infiltration of rain through the coal piles, producing acid mining drainage (AMD) which, due to its pH levels (<6), does not comply with the parameters stated in resolution 631 of 2015 (pH 6-9). The proposal to solve the problem presented was developed in 3 stages. In the first stage, after a characterization that was made of the coal leachate, an experimental development was carried out evaluating 3 different neutralizing agents (calcium hydroxide, sodium bicarbonate and sodium hydroxide) taking as variables the pH of the leachate sample and the volume of dosage necessary to adjust the pH to a value of 7, in this way, it was determined which agents have a lower volume of dosage finally, sodium hydroxide was selected as the best neutralizing agent for its low dosage volumes and lower costs for the neutralization of coal leachate.